Contract choice in the interwar US residential mortgage market - Jonathan Rose (Federal Reserve Bank of Chicago, 2018)
This paper studies mortgage contract choice in US history using a first-of-its-kind sample of residential loans from 1930 and 1940, linked to the decennial censuses. Contract choices reflected borrowers' reactions to the risks posed by different contracts. The majority of borrowers chose contracts with the longest available terms, despite required frequent amortization, likely in order to avoid refinancing risk and to maximize leverage. In contrast, the most creditworthy borrowers with high socioeconomic status preferred short-term contracts, confident that they could refinance at will. The combination of short terms and frequent amortization was unpopular, used disproportionately by the least creditworthy. Between 1930 and 1940, contract use shifted toward longer term contracts, reflecting the advent of federal involvement in the residential mortgage market.
Keywords: 330